2021
DOI: 10.3390/en14072024
|View full text |Cite
|
Sign up to set email alerts
|

Metadata Schemas and Ontologies for Building Energy Applications: A Critical Review and Use Case Analysis

Abstract: Digital and intelligent buildings are critical to realizing efficient building energy operations and a smart grid. With the increasing digitalization of processes throughout the life cycle of buildings, data exchanged between stakeholders and between building systems have grown significantly. However, a lack of semantic interoperability between data in different systems is still prevalent and hinders the development of energy-oriented applications that can be reused across buildings, limiting the scalability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 61 publications
0
34
0
Order By: Relevance
“…Some types of schemas include relational database schemas and ontologies. An ontology is a formal model that allows knowledge to be represented for a specific domain; while a schema describes the types of things that exist, the relationships between them, and the logical ways those things and relationships can be used together [21]. Data platforms are used for storing and managing large amounts of data organized in a uniform manner using a specific data schema or ontology.…”
Section: Figure 1 Overview Of the Review Methodology Highlighting Eight Stepsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some types of schemas include relational database schemas and ontologies. An ontology is a formal model that allows knowledge to be represented for a specific domain; while a schema describes the types of things that exist, the relationships between them, and the logical ways those things and relationships can be used together [21]. Data platforms are used for storing and managing large amounts of data organized in a uniform manner using a specific data schema or ontology.…”
Section: Figure 1 Overview Of the Review Methodology Highlighting Eight Stepsmentioning
confidence: 99%
“…The 24 selected data tools were grouped into four categories, based on the use cases in which the data are involved, as well as their functionality during the data curation process: 1) Terminology: A collection of standardized definitions and terms. 2) Ontology: An ontology is a formal model that describes the types of things that exist, the relationships between them, and the logical ways those things and relationships can be used together [21]. 3) Schema: A data schema is the skeleton structure that represents the metadata and hierarchy view of the entire dataset.…”
Section: Table 1 Seven Feature Aspects Used To Review the Data Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to development in occupant-centric metrics and occupancy sensing technologies, there has been significant advancement in the standardized representation of operational building data [27][28][29]. Many different forms of digital information are produced over the lifespan of a building, capturing design, construction, commissioning, operations and controls, maintenance, and audit information.…”
Section: Developments In Data Schemas For Buildingsmentioning
confidence: 99%
“…Some industry efforts have produced industry available protocols to improve the semantic data interpretability in building applications such as Brick Schema [15], Project Haystack [16], and the ontology of smart building (SBOnto) [17]. A thorough review of these efforts can be found in [18]. Nevertheless, those protocols lack of capabilities to standardize FDD-reported fault data.…”
Section: Introductionmentioning
confidence: 99%